Da’wah Through Fairy Tale; Study of Kak Ivan's Da’wah Method - Setia, Rizka Adhi; Rifa'i, Akhmad; Kristian Adi Putra (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2023)
He is giving da’wah to children certainly different from giving da’wah to adults. Giving da’wah to children must take an in-depth approach because their cognitive development is still preoperational, so it is necessary to use an understandable way while performing da’wah to children. The preoperational stage is the stage that begins around age two to seven years old. In this stage, children cannot yet use logic, transform, combine, or separate ideas. Hence, a child has not yet used his mind ultimately. One of the da’wah methods proper for children is the fairy tale method. Considering the background above, this study focuses on how giving da’wah through Kak Ivan’s fairy tale. This study used descriptive qualitative research using the data collection method through observation, interview, and documentation, and analyzing data using the interactive analysis method. The way Kak Ivan gives da’wah through fairy tales is unique because of his capability to imitate various sounds to captivate children. Kak Ivan starts his da’wah with an enchanting technique such as imitating the sound of a car, airplane, trumpet, a child, and an older man. This is quite rare to be found in other da’i. At the end of da’wah or the closing part, Kak Ivan uses puppets, and it is used in the final chapter to increase children’s focus that is already distracted in the middle of giving da’wah. Aside from being unique, da’wah through Kak Ivan’s fairy tale is a successful da'wah because of the positive effect on the mad'u, which can be applied in daily life. For example, asking friends to go to a sermon together, an initiative to help a friend by lending a pencil to someone who forgot to bring it, also can perform salah without having to be ordered by parents.